Booklet of “Si-JuRNalKu” (Preparation of Maternal-Neonatal Referrals in the Archipelago) to Increase Knowledge and Attitudes of Midwives - Melly Damayanti; Darwitri Darwitri (Aloha International Journal of Health Advancement (AIJHA), 2021)
The maternal mortality rate in Indonesia in 2019 was 205 per 100,000 live births and the infant mortality rate was 16 per 1,000 live births. Maternal mortality is still caused by delays (late detection of danger signs of pregnancy, delay in reaching health facilities and delay in getting adequate help). Delay in referral causes preventable maternal deaths. The purpose of this study was to analyze the effect of using the “Si-JuRNalKu” booklet (Preparation for Maternal Neonatal Referrals in the Archipelago Region) on the knowledge and attitudes of midwives in the Riau Archipelago Province in 2020. This study is a quasi-experimental study by applying pre-posttest with control. design groups. The research was conducted in August 2020 on midwives who work on islands spread over 5 districts in the Riau Archipelago Province. The sample was 30 midwives who were selected by purposive sampling technique, then divided into 2 groups. Data about knowledge and attitudes in the pre- and post-treatment phases were collected through filling out questionnaires, then analyzed using independent samples t-test and paired samples t-test. The results showed that after the treatment, there were differences in the level of knowledge and attitudes of the two groups, with a p value of 0.000. The average increase in knowledge and attitudes are 24.33 and 23.37, respectively. Furthermore, it was concluded that the “Si-JuRNalKu” booklet was effective in increasing the knowledge and attitudes of midwives in preparing referrals in the archipelago. It is hoped that midwives can use the “Si-JuRNalKu” booklet in preparing referrals. Keywords: midwife; “Si-JuRNalKu” booklet, knowledge; attitude